Serum Cardiac Troponin I in the Evaluation of Nonaccidental Trauma - Bennett, Berkeley L. (J Pediatr, 2015)
OBJECTIVE: To determine if troponin I is more often elevated in children with suspected nonaccidental trauma (NAT) compared with uninjured children of similar age, and describe associations between troponin I elevation and NAT injuries. STUDY DESIGN: Prospective 2-group study of children less than 2 years of age presenting to the emergency department with nonaccidental abdominal, thoracic, or intracranial injuries, and similarly aged uninjured children. Primary outcome was serum troponin I (≥0.04 ng/mL) using frozen blood samples from the 2 groups. Secondary outcomes included descriptive analyses of age, injury characteristics, and clinical appearance. RESULTS: There were 129 subjects; 60 injured patients and 69 uninjured patients. Groups had similar age and sex. Troponin I was elevated in 38% of injured children compared with 17% of uninjured children (P = .008). No uninjured patient over 3 months of age had elevated troponin I. Abdominal trauma, acute rib fractures, or the child’s ill-appearance in the emergency department were associated with having elevated troponin I. CONCLUSIONS: Troponin I is more often elevated in children with suspected NAT than uninjured children. Elevation of troponin I in children greater than 3 months of age with suspected NAT is concerning for trauma. Occult cardiac injury is more likely to occur in children with inflicted abdominal trauma, acute rib fractures, or ill appearance.